Unleashing creativity and innovation : nine lessons from nature for enterprise growth and career success - Birla, Madan (Wiley, 2014)
"Creativity and innovation are the keys to both organizational growth and successful careers. People understand this, but they do not know how to unleash their natural creative potential. Unleashing Creativity and Innovation: Nine Lessons from Nature for Enterprise Growth and Career Success will teach people to do just that using the tested and proven materials that Madan has been using with great success in workshops and one-on-one coaching. Readers will learn the four conditions for generating creative ideas and the practical three-step innovation process. The book will be filled with lessons such as: Trust that all resources for germinating creative ideas are within you Accept the risk inherent in expressing raw creative ideas See the big picture and think clearly the mind must be undisturbed To see the big picture and think clearly the mind must be undisturbed "- Resumé vydavatel